Intra-operative nasal compression after lateral osteotomy to minimize post-operative Peri-orbital ecchymosis and edema - L. Sowerby; L. M. Kim; W. Chow; C. Moore (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Introduction Post-operative periorbital ecchymosis and edema following rhinoplasty is a well-known sequela of surgery. Unfortunately, this can be a source of distress for patients, resulting in a longer post-operative recovery time and a delayed return to work. Trauma caused by lateral osteotomies is likely the most significant cause of periorbital edema and ecchymosis in rhinoplasty. There have been various strategies proposed to minimize swelling and ecchymosis with varying success rates and accompanied risks. Intraoperative nasal compression is one potential strategy that may reduce post-operative edema and ecchymosis with minimal risk. Objective To determine whether applying direct lateral nasal pressure intraoperatively immediately after performing lateral osteotomies reduces visible post-operative edema and ecchymosis. Methods A prospective, randomized blinded study on consecutive patients undergoing rhinoplasty with lateral osteotomies was conducted in a single academic tertiary care medical center. Each of the participants were randomized into direct pressure application post-lateral osteotomies on the right or the left hand side. Intra-operatively, direct lateral nasal pressure was performed on the pre-determined side for 5 min timed by stopwatch after osteotomy. Post-operatively, standard photographs were taken of the patient on post-operative days 1, 3, and 7. These photographs were then shown to 20 blinded-physicians and the degree of ecchymosis and edema was graded using a previously published scale. Results A total of 16 patients were included in this study. Based on our blinded-grading, 11 of the 16 patients had a clear global improvement in the degree of peri-orbital post-operative edema and ecchymosis with compression post lateral osteotomies. Based on the 3 blinded expert reviewers, Periorbital ecchymosis was significantly decreased on the ipsilateral side of pressure application in 10 of the 16 patients, and periorbital edema was significantly decreased in 13 of the 16 patients. The differential degree in periorbital ecchymosis was most pronounced on post-operative day 7. Patient factors such as gender, age, skin color, history of nasal trauma, side of pre-operative nasal deviation, and smoking status did not have a significant influence on the effect of pressure application post lateral osteotomies. Conclusions Application of direct continual lateral nasal pressure intraoperatively after performing lateral osteotomies can help reduce post-operative edema and ecchymosis up to post-operative day 7. This may lead to an overall improved appearance and subsequently an improved post-operative experience for the patient. Although the effect may be variable to some degree, this is an intervention with no additional risks involved and thus can be used in a safe manner.